SELF ASSESSMENT TERKAIT GAP KOMPETENSI PERAWAT KLINIK LEVEL III SELF ASSESSMENT OF GAP COMPETENCY BY CLINICAL NURSES LEVEL III - Lumbantobing, Valentina; Yudianto, Kurniawan; Nani, Ai (Journal Nursing Care and Biomolecular, 2019)
Introduction: Problems that occur in patients, advancement of knowledge, development of new tools, technology and health procedures are challenges for professional professionals to improve their competence. A competent nurse in accordance with the field and level is one of the elements supporting the patient's authority. The higher the career path of a nurse hopes the more expert in carrying out and providing nursing care in accordance with his clinical authority. Methods: The purpose of this study was to find out the nurse's competency gap on clinical authority that had been determined at the Level III Nurse Clinic in the Intensive area in one hospital in Bandung. This research is a kind of quantitative descriptive research. The population in this study were all level III clinical nurses in the intensive area of one hospital in Bandung, the sampling in this study was total sampling so as to obtain as many as 75 respondents. Data collection was conducted using a research instrument in the form of a questionnaire taken from the details of clinical authority charged to level III clinical nurses in the Intensive area. Data is analyzed univariately using proportions or percentages. Results and Analysis: The results of this study indicate that out of 32 types of competencies based on clinical authority at level III clinical nurses in the intensive care area, there is a competency gap in 20 types of competencies with varying percentages. The conclusion of this study is that there is a competency gap in level III clinical nurses in the intensive care area of one hospital in Bandung. Discuss: it is recommended to the nursing committee to plan the Continuing Professional Develompment program by prioritizing the highest competency gap percentage, namely managing patients with CRRT tools, Plasmapheresis, research methodology and using research results in nursing care.